Percepção espacial como instrumento participativo de planejamento urbano - Lopes, Davi Emerich (2008)
This paper is all about spatial perception in order to be used at participative process of urban planning. The spatial perception to deal with the relationship between human being and space to identify needs, desires, opinions, appropriation level, to have a basic grasp of citizen and so on. The urban process has taken the human being to adapt to transformed space, instead of to adapt to space to human being, to take for granted the consequences of life quality. Some of the authors like Kevin Lynch and Amos Rapoport show that the built space should be adapted to human needs searching spatial quality. For this, the supplied subsidies by spatial perception are valuable to planner to take a decision. This subsidies come form population introducing different way to popular participation at planning process. There are many techniques to get the population perception. For instenee: the interviews, the mental maps, the photographs, etc. It is established a methodology strategy in each case according to the specific study s object and the research purpose. To discuss the perception spatial as participative process are analyzed three brazilians experiences which one is involved the public power; one of them at Região Metropolitana de Vitória (ES), the other at Santo André (SP) and at last Araraquara (SP). After all, the feasibility of the spatial perception as participative instrument is argued theoretically studying the subsidies supplied, the quality of popular participation and the condition for its introducing.